Heromice #11: Revenge of the Mini-Mice - Stilton, Geronimo (Geronimo Stilton Heromice, 2017)
Super Swiss slices! Tony Sludge and the sewer rats have invented a new device: a shrink ray that can turn things tiny! Tony has a plan to use it to steal all of Muskrat City's gold. It's up to the Heromice to stop him, but they'd better be careful the sewer rats don't turn them into mini-mice first!